A Feasibility study on Son-Ria Herbal Chocolate Bar - Bacudio, Lindley R.; De Guzman, Rhedd Jorge L.; Espino, Eloisa E.; Sanchez, Seymour B. (College of Engineering, 1998)
Chocolate is a solid or semisolid food prepared by the fine grinding of roasted, shelled beans of the cacao, or cocoa, tree. Although chocolate and cocoa are commonly regarded as very different foods, they differ only in the amount of cocoa butter they contain. When chocolate liquor is subjected to hydraulic pressure until its cocoa butter content is reduced from about 54% to 24% or less, the residue forms a solid mass called press cake. This cake is broken, pulverized, cooled and sifted, producing commercial cocoa powder. Chocolate is made with chocolate liquor whose fat content has not been reduced. SON-RIA Herbal Chocolate Bar, a healing breakthrough in food and nutrition, is both a chocolate bar and a natural health supplement made from an idea of Filipino Inventors Society (FIS) member Lorenzo L. Cunanan. The product comes in three variations: regular, with carrot, with Korean red ginseng. This consists of premised chocolate, pop rice, ad solutions of sambong, lagundi, and pandan, which make it unique, plus the additional carrot and ginseng, depending on the kind. Despite the difficulty inn product preservation, the market for chocolates has remained stable. Data shows an increasing demand for chocolate and a remarkable drop in chocolate imports. With an annual production capacity of 1.5 to 1.6 thousand metric tons of chocolate, the project will be able to maintain a market share of 29%. The product will be exclusively distributed by Asset Marketing Corp. to major supermarkets and sari-sari stores in the National Capital Region, targeting young consumers from 5-24 years old and those belonging to income brackets A, B, and C. Aggressive marketing is required for the first year with an estimated budget of P8,330,000, decreasing to P3,035,000 for the second year to P1,567,000 for the last three years. The Major processes involved in the manufacture of this chocolate are grinding the premixed chocolate, mixing the ingredients, refining the course chocolate paste, conching and kneading, and molding into bars. Two major machines are used, namely, the Universal 2000 Refiner/Conche and the SIMA600 Chocolate Molding Plant. To be able to meet the daily demand, four batches of production are needed. This would require two shifts per day for the production department, as dictated by the rated capacities of the machines. Other auxiliary equipment is also necessary for materials handling, storage, packaging, and other functions. At least 35 jobs are offered by the project: 16 workers are directly involved in production, 11 are classified as administrative employees, and the rest are for maintenance and security. The plant will be located at a 3,410 m2 area in Norzagaray, Bulacan, just enough for the 2,835 m2 space requirement for the project and for further expansion. The total project cost for the first year is P181,972,820.13, which is broken down into the following: P38,491,300 for the cost of investment, P10,792,036.48 for the operating expenses, P2,392,000 for the administrative expenses, P113,754,500 for the manufacturing expenses, and a 10% contingency cost amounting to P16,542,983.65. Sources of financing include loans made through the Department of Science and Technology-Invention Development Assistance Fund (DOST-IDAF) and the DOST-Invention Financing Fund (IFF) and the rest will be through equity. A total of P84,493,600 common shares at P1 par value will be sold to private investors. Dividends will be declared annually at a rate of 25% of the net income. The net present value (NPV) of the project is P4,503,355.42. Payback period is 3.04 years and the internal rate of return (IRR) is 22.35%. Since the NPV is positive and the IRR is greater than the minimum attractive rate of return (MARR) of 20%, the project is considered financially acceptable. Chocolate manufacturing becomes socially profitable in light of the current administration?s focus on food security, one of the main programs designed for poverty alleviation. The company would pay taxes annually amounting to 43% of its gross income to the government and the employees would pay its income taxes amounting to 1-% of their salaries. Suppliers capture 87-91% of the annual expenses of the plant while the company employees chuck up 4-6% of the gross profit, in terms of their salaries and benefits, for the duration of the project. Given a fixed cost of P66,356,300, a variable cost of P114,991,095 (P3 per unit), and a production volume of 38,225,000 bars (in 1999) at a selling price of P6.00 per unit, the break even volume (BEV) for the project was computed at a value of 22,118,767 bars. The safety margin for the company, if there is a change in demand (and all other factors such as price remain the same), is pegged at 42%. The break-even selling price (BESP), the minimum sales price for the product, is derived to be P4.74 and the safety margin for price changes is 21%. The break-even sales is calculated to be P181,186,500. The corporate form is the most favored for this project since chocolate manufacturing is capital-intensive. This form, which is the most suited for big operations such as this project, is generally in a stronger position to obtain loan financing because of the stability of business life, bigger capital base due to the pooling of capital, and pooling of management talents and business contacts. The BDES Corporation, coined from the initials of the project proponents, will handle the implementation of the project with a set of top-caliber managers to be hired to foresee that the plant functions are being undergone based on the company?s charter. The stockholders do not manage the business for the project. Management is handled only by the Board of Directors, or by the officers elected by the board. The directors manage the affairs of the corporation only as a group or as a board, and not individually. From the feasibility study on the SON-RIA Herbal Chocolate Bar, the proponents of the study conclude that the project is worth undertaking based on the results of the market, technical, financial, social profitability, and organization and management studies conducted.